2016
DOI: 10.2991/jrnal.2016.3.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Feature Acquisition From Facial Expression Image Using Convolutional Neural Networks

Abstract: In this study, we carried out the facial expression recognition from facial expression dataset using Convolutional Neural Networks (CNN). In addition, we analyzed intermediate outputs of CNN. As a result, we have obtained a emotion recognition score of about 58%; two emotions (Happiness, Surprise) recognition score was about 70%. We also confirmed that specific unit of intermediate layer have learned the feature about Happiness. This paper details these experiments and investigations regarding the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…As this miniature sensor has small dimensions of 2.7 x 3.2 x 1.4 mm (W x L x H), 40 units are densely arranged at sampling points on the face capture mask, as shown in Figure 5. Following the standard practice of face recognition [24,25,33], we picked eyebrows, cheeks and around eyes and mouth as the sampling points of photo reflective sensors. We ensure that the sensors do not come into contact with the eyes, nose and mouth of the mask wearer.…”
Section: Facial Expression Identification Methodsmentioning
confidence: 99%
“…As this miniature sensor has small dimensions of 2.7 x 3.2 x 1.4 mm (W x L x H), 40 units are densely arranged at sampling points on the face capture mask, as shown in Figure 5. Following the standard practice of face recognition [24,25,33], we picked eyebrows, cheeks and around eyes and mouth as the sampling points of photo reflective sensors. We ensure that the sensors do not come into contact with the eyes, nose and mouth of the mask wearer.…”
Section: Facial Expression Identification Methodsmentioning
confidence: 99%
“…CNN is good at processing images [26]. Traditional face recognition methods show poor results when facing complex scenes.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…In this study, we focus on research on human facial expression recognition [11] to provide autonomous learning support through teacher-type robots. In particular, methods based on deep learning have been widely used in research on facial expressions, and have shown high performance in image recognition and image classification Convolutional neural networks (hereafter, this is called CNN) have been proposed [12]. However, conventional research on facial expression recognition has focused only on the seven basic emotions of anger, disgust, fear, happy, sad, surprise, and neutral (hereafter referred to as the seven basic emotions), and has not focused on perplexion.…”
Section: Introductionmentioning
confidence: 99%